O ensino de expressões idiomáticas à luz da lexicografia pedagógica - Matias, Gislaine Rodrigues [UNESP]; Silva, Maria Cristina Parreira da [UNESP] (My University, 2011)
In the current context of lexicographical studies, there have been increasing discussions concerning the issue of the relationship between theoretical knowledge of the lexicon and pedagogical practices involved in its teaching. However, in this context, the special lexicon of Portuguese such as neologisms, foreign words, slang and idioms has received little attention from researchers. There are many theoretical studies on each one of these phenomena, but few studies aim at an organization and inclusion of special units in the teaching of Portuguese. For this reason, this article presents a reflection on the teaching of idioms, and, despite the widely held belief that dictionaries are only needed for the teaching of foreign languages, the article suggests the implementation of special dictionaries for the teaching of Portuguese Language in elementary education.

No contexto atual dos estudos lexicográficos, cada vez mais vêm sendo discutidas questões que tratam da relação entre os conhecimentos teóricos sobre o léxico e as práticas pedagógicas envolvidas no seu ensino. Porém, nesse contexto, ainda é dada pouca atenção ao léxico especial da Língua Portuguesa, como os neologismos, os estrangeirismos, as gírias e as expressões idiomáticas. Há muitos estudos teóricos sobre cada um desses fenômenos, mas são raros os estudos que visam a uma organização e inclusão dessas unidades especiais no ensino da Língua Portuguesa. Por conta disso, este artigo tem o objetivo de apresentar uma reflexão sobre o ensino de expressões idiomáticas e aplicação de dicionários especiais para o ensino de Língua Portuguesa no nível fundamental, embora muitos acreditem que é apenas para o ensino de línguas estrangeiras que esses dicionários são necessários.
Keywords: dicionários especiais; expressões idiomáticas; lexicografia pedagógica; special dictionaries; idiomatic expressions; pedagogical lexicography